The Memoirs (Ruznāma) of Ghiyāth al-Dīn Naqqāsh on His Journey to China During the Timurid Era (822-825 AH / 1419-1422 AD) and Its Historical and Cultural Value - Aykut, Abdulsait (Jordan Journal for History and Archaeology, 2024)
This article focuses on the identity of Ghiyāth al-Dīn Naqqāsh and discusses different versions of his text (Ruznāma), its translations into Turkish and Western languages, and previous research. The article also discusses the contents of the Ruznāma, Timurid-Chinese relations and Ghiyāth al-Dīn Naqqāsh’s observations about Chinese customs, city planning, and the ceremonies of hospitality in China; and compares those details in other documents and sources studied by historians of Chinese civilization.